A tale of narrative annexation; Stories from Kisar Island (Southwest Maluku, Indonesia) - van Engelenhoven, Aone; Nazarudin, Nazarudin (Wacana, Journal of the Humanities of Indonesia, 2016)
This paper discusses strategies of appropriation of narrative heritage in literate and narrative histories on the island of Kisar. It shows that notwithstanding their sometimes literate characteristics, storytelling in competitive contexts still follows strategies that are typical for oral performances. This paper questions in how far literate and narrative historiographies can and ought to be separated from each other in Southwest Maluku.